Host–Guest Orientations of Community‐based Tourism Products: A Case Study in Bali, Indonesia. (10th April 2017) - Ernawati, Ni Made; Sanders, Dale; Dowling, Ross
Abstract: This research provides a greater understanding of community‐based tourism products through an examination of the perceptions of the host communities and tourists. Using a survey, data were collected measuring community‐based tourism products through nine elements including attractions, travel services, transport, accommodation, food and beverage, souvenirs, packaging, amenities and people. The overall results indicate that there was considerable agreement on most product items. The tourists clearly identified their expectations and were supportive of a sustainable industry; however, they were also concerned about safety and hygiene. The host communities were aware of the intrinsic value of the tourist attractions in their villages but lacked the confidence to share them with visitors.